Electrochemical characterization of a CFY-stack with planar electrolyte-supported solid oxide cells in rSOC operation. (5th July 2018) - Preininger, Michael; Subotić, Vanja; Stoeckl, Bernhard; Schauperl, Richard; Reichholf, David; Megel, Stefan; Kusnezoff, Mihails; Hochenauer, Christoph
Abstract: In this study, a ten-layer SOC-stack, consisting of large planar electrolyte supported cells (ESC) and CFY interconnects, was operated in both fuel cell and electrolysis modes considering steam-, co-, and CO2 -electrolysis. Different gas mixtures containing H2, H2 O, CO, CO2, and N2 were applied for this purpose, and an extensive analyses were performed at two temperatures, 800°C and 850°C. Under these operating conditions, independent Electrochemical Impedance Spectroscopy (EIS) measurements were performed on the stack as a whole, and several cells within the stack concurrently. In order to analyze the losses that occurred during operation, measured impedance values were analyzed, and an electrical equivalent circuit (EEC) for ESCs was applied to the measured impedance spectra. Finally, the electrochemical impedance measurements were performed at both OCV and elevated current densities. Highlights: Concurrent measurement of independent EIS on several cells in a multi-cell stack. Electrochemical analyses of an SOC stack at OCV and elevated current densities. Hybrid EIS which combines the advantages of galvanostatic and potentiostatic EIS. Reversible operation under various conditions in fuel cell and electrolysis mode.